1999
DOI: 10.1038/sj.bjc.6690452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of synergism between cisplatin and gemcitabine in ovarian and non-small-cell lung cancer cell lines

Abstract: 2′,2′-Difluorodeoxycytidine (gemcitabine, dFdC) and cis -diammine-dichloroplatinum (cisplatin, CDDP) are active agents against ovarian cancer and non-small-cell lung cancer (NSCLC). CDDP acts by formation of platinum (Pt)–DNA adducts; dFdC by dFdCTP incorporation into DNA, subsequently leading to inhibition of exonuclease and DNA repair. Previously, synergism between both compounds was found in several human and murine cancer cell lines when cells were treated with these drugs in a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 27 publications
6
112
0
2
Order By: Relevance
“…Hypoxic tumors have poorer clinical prognosis, are often resistant to both radiation and chemotherapy (33), and are more likely to metastasize (34). The nucleoside analogs 5-FU and dFdC are used clinically in the treatment of solid tumors (35,36), and we have shown that elevated expression of cN-I increases the IC 50 for 5-FU 5.2-fold and the IC 50 for dFdC 21.6-fold in the HEK cells (Table V). Although the effect of hypoxia on drug resistance in the context of cN-I activity remains to be investigated, this study provides support for the hypothesis that increased ADP concentrations in ischemic tumors may facilitate dephosphorylation of several nucleoside-based drugs and lower their pharmacological efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic tumors have poorer clinical prognosis, are often resistant to both radiation and chemotherapy (33), and are more likely to metastasize (34). The nucleoside analogs 5-FU and dFdC are used clinically in the treatment of solid tumors (35,36), and we have shown that elevated expression of cN-I increases the IC 50 for 5-FU 5.2-fold and the IC 50 for dFdC 21.6-fold in the HEK cells (Table V). Although the effect of hypoxia on drug resistance in the context of cN-I activity remains to be investigated, this study provides support for the hypothesis that increased ADP concentrations in ischemic tumors may facilitate dephosphorylation of several nucleoside-based drugs and lower their pharmacological efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…After harvesting, nucleotides were extracted and quantitated with HPLC as previously described . Incorporation studies were performed using 96-well filter plates essentially as described previously (Van der Wilt et al, 1993;Van Moorsel et al, 1999a). A total of 1.0 Â 10 5 cells per well were plated in a volume of 100 ml, whereafter 100 ml of [ 3 H]gemcitabine containing medium (4 Ci mmol À1 ) was added resulting in final concentrations of 0.1 or 1.0 mM.…”
Section: Dfdctp Accumulation and Retentionmentioning
confidence: 99%
“…Phase I studies evaluating this combination in relapsed and refractory HL and NHL have also reported higher RRs (Aviles et al, 2004;Emmanouilides et al, 2004) compared to either agent given as monotherapy (Fossa et al, 1999;Santoro et al, 2000;Savage et al, 2000;Zinzani et al, 2000). The mechanisms underlying this synergy may be due to increased incorporation of gemcitabine into DNA and RNA, and increased cisplatin -DNA adduct formation by inhibition of exonuclease and DNA repair (van Moorsel et al, 1999). Given their synergism, absence of significant overlapping toxicities and non-cross-resistance with other regimens, gemcitabine in combination with cisplatin, presents an attractive treatment option.…”
mentioning
confidence: 99%